PEMROGRAMAN KEMBALI PASAR HEWAN JATINEGARA: HEWAN PELIHARAAN SEBAGAI MAGNET KOMUNITAS - Vania Diandra Abigail; Olga Nauli Komala (Jurusan Arsitektur dan Perencanaan, 2022)
Jatinegara animal market is the oldest animal market in Jakarta, however the condition now are lack of visitors. This deserted market makes the surrounding buildings abandoned and many buildings are rented out. This is because the physical condition of the market which is shabby, slippery and irregular. The market stalls take up the pedestrian area which disturbs the surrounding activities. The dimensions of the market stall are also one of the main problems making the experience of buying and selling animals less comfortable. The solution in this case uses urban acupuncture by making the market an attraction for the Jatinegara area. Re-programming is a way to make adjustments from existing programs and then insert new programs such as animal playgrounds, animal contests, bazzars, festivals, pet hotels, pet foster & care, pet grooming, and adoption centers as the market attraction. In this case using animals as a main attraction in the market because it has a role as a social lubricant for human society. Analysis of market conditions includes analysis of existing markets and the relationship between animals and humans which are done by observation, interviews, literature studies, studies of precedents, and mapping. The design of a market with an interaction space between animals and humans are the solution in the Jatinegara Animal Market area. Keywords: interaction space; Jatinegara Animal Market; pets; re-programming; urban acupuncture Abstrak Pasar hewan Jatinegara merupakan pasar hewan tertua di Jakarta, namun kondisinya sekarang semakin sepi pengunjung. Pasar yang sepi ini membuat bangunan sekitar menjadi terbengkalai dan banyak bangunan disewakan. Hal ini dikarenakan kondisi fisik pasar yang kumuh, licin dan tidak beraturan. Kios-kios pasar mengambil area pedestrian yang membuat aktivitas di sekitarnya menjadi terganggu. Dimensi kios pasar juga menjadi salah satu masalah utama membuat pengalaman jual beli hewan menjadi kurang nyaman. Penyelesaian dalam kasus ini menggunakan urban akupunktur dengan menjadikan pasar sebagai daya tarik kawasan Jatinegara. Re-programming merupakan salah satu cara untuk melakukan penyesuaian dari program yang sudah ada dan kemudian menyisipkan program-program yang baru seperti taman bermain hewan, kontes hewan, bazzar, festival, pet hotel, pet foster & care, pet grooming, dan adoption center sebagai daya tarik pasar. Dalam hal ini, hewan sebagai daya tarik utama yang berperan sebagai social lubricant. Analisis terhadap kondisi pasar meliputi analisis existing pasar dan hubungan antara hewan dengan manusia yang dilakukan dengan cara observasi, wawancara, studi pustaka, studi preseden, dan mapping. Perancangan pasar dengan ruang interaksi antara hewan dengan manusia merupakan hasil dari penyelesaian masalah kawasan Pasar Hewan Jatinegara.